2018
DOI: 10.1186/s40748-018-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of milrinone in neonates with persistent pulmonary hypertension of the newborn - a randomised controlled trial pilot study (MINT 1): study protocol and review of literature

Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is a relatively common condition which results in a mortality of up to 33%. Up to 40% of infants treated with nitric oxide (iNO) either have a transient response or fail to demonstrate an improvement in oxygenation. Milrinone, a selective phosphodiesterase 3 (PDE3) inhibitor with inotropic and lusitropic properties may have potential benefit in PPHN. This pilot study was developed to assess the impact of milrinone administration on time spent on iNO in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…36 There is currently lack of data in the newborn population, but this agent may become an interesting avenue to address patients with severe PH and underlying RV dysfunction leading to mortality. [36][37][38] Long-term evolution of PH in newborns with omphalocele remains unknown. Although some have suggested that PH resolves, 2 late PH has been described in some graduates of the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…36 There is currently lack of data in the newborn population, but this agent may become an interesting avenue to address patients with severe PH and underlying RV dysfunction leading to mortality. [36][37][38] Long-term evolution of PH in newborns with omphalocele remains unknown. Although some have suggested that PH resolves, 2 late PH has been described in some graduates of the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, we note that only 33% of the infants in each group had OI > 10 and would be eligible for participation in ongoing/proposed randomized trials of milrinone in CDH or neonatal pulmonary hypertension. 17,18 Finally, our ability to interrogate cardiac performance was limited by a less than robust ECHO dataset. At our center, ECHO measures of right and left ventricular function are not routinely captured in a standardized manner for all neonates with CDH.…”
Section: Discussionmentioning
confidence: 99%
“…A power calculation was performed for our study. Using an anticipated incidence of PPHN in a high risk cohort of 0.7% compared to a background incidence in the general population of 0.05% [ 24 ], 308 participants will be required for this study (80% confidence and a type I error rate of 0.05).…”
Section: Methodsmentioning
confidence: 99%